Meningkatkan Hasil Belajar Kreatif Siswa Melalui Model PBL Gereja Sebagai Umat Allah FaseF SMKN 1 Kelam Permai - Haryono Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education is very important in this era of globalization and is even included in the basic needs of every human being because by obtaining education humans will be able to improve their quality of life. Education is also one of the supporting factors for a country's progress, with a country's high level of education it can produce quality human resources and contribute to developing the country. Catholic Religious Education is an effort made so that students have the ability to build a more faithful life. Christian and devoted to God Almighty in accordance with the teachings of the Catholic Church. Building a life of Christian faith means building loyalty to the Gospel of Jesus Christ, which has a single concern, namely the Kingdom of God. The Kingdom of God is a situation and event of salvation: a situation and struggle for peace and justice, happiness and prosperity, brotherhood and loyalty as well as environmental preservation, which is longed for by everyone from various religions and beliefs. Catholic Religious Education lessons are also not included in the subjects that take part in the State Examination. This causes students to underestimate Catholic Religious Education lessons. In situations like that, teachers must be good at creating situations, creative and good at having methods so that PAK learning can be more interesting and arouse students' interest. Based on the researcher's experience of teaching at SMK N 1 Kelam Permai, many students obtained below average learning outcomes and students had little interest in the Catholic religious learning process. They were less interested in participating in PAK learning. They also underestimate PAK learning because they prioritize other subjects. To overcome the problems mentioned above, one of the alternatives proposed by researchers is learning using the Problem Based Learning model with the reward method, which aims to ensure that students' learning outcomes are good and they have a high interest in learning. The Redward method intended in this research is an educational tool for educational efforts to achieve satisfactory learning outcomes and change students' interest in learning for the better. By giving this prize, it is hoped that students will be more interested in participating in lessons, especially in studying material about the Church as God's people. The objectives of this research are 1). PBL learning using the reward method on Church material as God's people can improve student learning outcomes creatively. 2). Increasing creative student learning outcomes in Catholic Religious Education by providing rewards for church material as God's people.3). Knowing students' reactions to the use of the Problem Based Learning (PBL) method by providing rewards to improve students' creative learning outcomes and interest in phase F of SMK N 1 Kelam Permai. In particular, in the material "The Church as God's people" it is hoped that students will be able to find themselves, recognize and accept themselves as members of God's people, and work together in efforts to develop themselves as members of the Church in accordance with God's plan. The Problem Based Learning (PBL) learning model by providing rewards can overcome problems in motivating students to be more creative in learning. Redward's way of working is in accordance with the way students learn and encourages students to be more enthusiastic and creative in learning so as to improve student learning outcomes, especially in Catholic religious education.